Dynamics of changes in the structure of mental illnesses among servicemen treated in the hospital of the psychiatric department of the military medical clinical center of the northern region - HaydabrusАndriy V. (Psychiatry, Neurology and Medical Psychology, 2020)
Against the backdrop of growing military conflict, hostilities are the most stressful factor in deteriorating mental health. For 7 years (from 2012 to 2019) a study of data from 3587 inpatients who served in peacetime, participated in hostilities and served during the armistice. The average age of servicemen differed significantly depending on the period of service, was 26.5 years in 2012 and increased to 34.2 years in 2019. In peacetime, diseases predominantly related to neurotic, stress-related and somatoform disorders (F40-F48), adult personality disorders and behavioral disorders (F60-F69). The drug problem comes to the fore during the fighting in late 2014 and 2015. The total number of patients with drug problems was 46.2% among all hospitalized in 2014 and 2015. During the same period, 24.2% of all hospitalized patients had neurotic stress-related and somatoform disorders (F40-F48). As active hostilities decreased, the number of these disorders increased. In 2019 and amounted to 50.8% of servicemen treated in hospital. In the hospital, we observed an increase in mental and behavioral disorders due to the use of psychoactive substances (mainly alcohol, opiates), the number of such patients increased in the overall structure of diseases to 21.5% in 2019. For the first time, a significant amount of data from servicemen was analyzed and the obtained material demonstrates the need to involve narcology specialists in the rehabilitation process.